La crisi dell’identità sociale tra pregiudizi, xenofobie e razzismi. L’inclusione dell’altro in tempo di crisi in Italia e Spagna - Bello, Valeria (SocietàMutamentoPolitica, 2015)
By focusing on the sociological literature investigating the effects of processes of identity constructions on the formation of prejudice, racism and xenophobia, this article compares attitudes towards immigrants in Spain and Italy for the years before and after the recent socio-economic crisis in Europe. It highlights how different ways of framing its own and others identity, produce for people different results in terms of attitudes towards outsiders. In particular, from the statistical analysis of European Social Survey data, it is clear that the Italian society is more prejudiced towards migrants than the Spanish one, and mainly shows a cultural or ethnic type of racism, while in Spain people have become more inclusive in a decade time. However, the findings also illustrate that, during the years of the socio-economic crisis, the figures of extremist individuals have increased in both countries. Despite this, Spain has shown an important rise of inclusive attitudes towards immigrants; while, in Italy, if renewed and more inclusive immigration policies are formulated, the situation could improve.